HUBUNGAN WAKTU TANGGAP PERAWAT DALAM PENANGANAN PASIEN FRAKTUR TERBUKA DENGAN RESIKO TERJADINYA SYOK HIPOVOLEMIK DI IGD RSUD DR ACHMAD MOCHTAR BUKITTINGGI TAHUN 2015 - Aldo Yuliano; Nova Erlina Sasra (JURNAL KESEHATAN PERINTIS, 2015)
Open fracture is a fracture with a clearly visible translucent skin, which could be contaminated by the environment. Cause of death patient emergency serious condition that is 50% on the way to the hospital, 35% due to trauma and also 50% died at the time of the incident or a few minutes after the incident (Pusponegoro, 2008). Relief on emergency patients have a service standard time known as the response time (Response Time) is the time span necessary services ranging from determining triage nurse to complete the process of handling emergency patients (fractures). The purpose of this study was to determine whether or not there is a relationship proper response time handling the risk of shock. This study uses descriptive correlative. This research was conducted at IDG Hospital Dr Achmad Mochtar Bukittinggi in June-July 2015. The research sample totaled 26 ER nurses were selected using total sampling technique. Collecting data using observation sheet in accordance with the criteria respondent sample. The results showed the majority of nurses do not fracture treatment in patients timely namely 65.4%, while for the risk of shock that is 61.5%. Test results using a chi-square statistic values ​​obtained Fisher's Exact Test = 0.046 (<0.05) thus conclude that there is a relationship of response time nurse in the treatment of patients with open fractures risk of hypovolemic shock. Of the research are expected to lead in order to make observations to the members of his team about the time the action is used for taking action on an open fracture patients so as to minimize the risk of hypovolemic shock.